Reconceptualizing the Role of the University Language Teacher in Light of Generative AI - Mark Tutton; Doron Cohen (Education Sciences)
This paper reconceptualizes the role of the teacher in the university foreign language classroom in an age of generative AI chatbots and automatic translation tools. We call for a reconceptualization of this role based on two factors: the unique social interactivity of the university language classroom and the need for effective instruction on how to use Intelligent Computer-Assisted Language Learning (ICALL) tools outside of the classroom. We argue that the teacher must master and integrate these two different modes of teaching and learning. Interpersonal exchanges in class respond to the need for real-time human interaction and relatedness in language learning and so cannot, and should not, be wholly replaced by chatbots. Rather, these sorts of exchanges must form a cornerstone of on-campus foreign language pedagogy. In contrast, teachers must also be able to leverage the benefits of learner-facing AI tools, especially for use outside of the classroom, given the learning gains associated with them. We provide detailed examples of how this dual approach can be realized and propose a five-step approach for incorporating AI into university language pedagogy.